Alleviating moisture stress under irrigation scheduling and crop establishment techniques on productivity and profitability of wheat (Triticum aestivum) under semi-arid conditions of western India - A, RAJANNA G; S, DHINDWAL A; NARENDER, NARENDER; D, PATIL M; L, SHIVAKUMAR (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was carried out in semi-arid condition of Hisar during two consecutive years (2012-13 and 2013-14) to assess the performance of wheat under varied irrigation schedules with crop establishment techniques. In present study, wheat planted on beds (FIRBS) resulted in 15-19% increase in grain yield than minimum and conventional tillage systems but the margin was slightly lower and it was statistically at par with zero tillage (ZT). Inclusions of beds in wheat cultivation have led to improved growth indices, growth and yield parameters over conventional and reduced tillage practices. Adoption of ZT under semi-arid conditions led to 12-48% (2012-13) and 27-68 % (2013-14) higher net returns to farmers by reducing the cost incurred on the primary tillage operations. Consumptive water use was reduced by 9-12% besides improved water use efficiency (WUE) and irrigation water productivity (WPI) under beds than conventional tillage. Improved soil health concerning bulk density, soil organic carbon and total NPK status were perceived under ZT wheat. Growth indices, growth and yield parameters, grain and biological yields of wheat showed improvement under application of irrigation at higher moisture regime of CRI+IW:CPE=0.90 over lower moisture regimes.